In defense of empire: government press collaboration in the British win the war efforts in Nigeria during the second world war - Mordi, Emmanuel Nwafor (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper examines the collaboration between the Nigerian press and imperial Britain for the victory of the Allies over Nazi Germany during World War II. Guided by the descriptive-analytic, historical approach, archival sources and information provided by national dailies, which are available at the Nigerian National Archives, Ibadan, as well as secondary sources on the subject were interrogated to produce the work that is embodied in this essay. Against the background of the conventional wisdom that Nigerians were so far away from the war theater that they were indifferent to appeals for self-sacrifice demanded by the war, the study proposes the counter argument that Nigerians made substantial sacrifices which contributed to Allied victory over Nazism. The point is illustrated with the Nigeria Win the War Fund, which was a scheme designed for the purchase of war equipment. It was initiated and sustained by the press, but inaugurated with active government support and encouragement, contrary to the standard notion of frosty government-press relations during the war.